Paid Parental Leave evaluation: Phase 1 - McVicar, D; Broom, D; Baxter, Janeen; Hewitt, B; Zadorozny, M; Martin, B; Baird, M; Xiang, N; Walter, M; Whitehouse, G; Heron, A; Strazdins, L; et al. (publications.research@fahcsia.gov.au, 2012)
There were 295,700 births registered in Australia in 2009, reflecting a total fertility rate of 1.90 babies per woman. About 45 per cent of Australian births are first births (ABS 2009c). Some 65 per cent of births in 2009 were to currently married mothers, with many of the remaining 35 per cent of births to mothers in de facto relationships. The labour force participation rate of women has been increasing over the past two decades, reaching 59 per cent in February 2011. The increasing tendency of mothers to be in the paid workforce has been a key factor in the overall rise in women’s labour force participation. Between 1996 and 2006 the participation rate of mothers with children aged 0 to 14 years rose from 59 per cent to 64 per cent. In February 2011, 63 per cent of the 726,200 Australian families with one child under 15 had both parents in the workforce.
Occasional Paper No. 44
Occasional Papers
Keywords: Families -- Composition; Benefits and Payments -- Family payments; Employment -- Parental leave; Life Events -- Birth/adoption; Disadvantage, adversity and resilience; Families and relationships; Labour market; Life Events; Employment; Benefits and Payments; Families; Birth/adoption; Composition; Parental leave; Family payments; Employment and unemployment; Adversity and resilience; Families and relationships; Dsiadvantage, adversity and resilience